Therapeutic antibodies as a treatment option for dengue fever. Issue 11 (November 2013) - Chan, Kuan Rong; Ong, Eugenia Z; Ooi, Eng Eong
Dengue fever is the most prevalent mosquito-borne viral disease globally with about 100 million cases of acute dengue annually. Severe dengue infection can result in a life-threatening illness. In the absence of either a licensed vaccine or antiviral drug against dengue, therapeutic antibodies that neutralize dengue virus (DENV) may serve as an effective medical countermeasure against severe dengue. However, therapeutic antibodies would need to effectively neutralize all four DENV serotypes. It must not induce antibody-dependent enhancement of DENV infection in monocytes/macrophages through Fc gamma receptor (FcγR)-mediated phagocytosis, which is hypothesized to increase the risk of severe dengue. Here, we review the strategies and technologies that can be adopted to develop antibodies for therapeutic applications. We also discuss the mechanism of antibody neutralization in the cells targeted by DENV that express Fc gamma receptor. These studies have provided significant insight toward the use of therapeutic antibodies as a potentially promising bulwark against dengue.